Regulating foreign direct investment to achieve technological sovereignty in the European Union - A. A. Makarova (Модернизация, инновация, развитие, 2025)
Purpose: is to assess the European Union's approach to strengthening technological sovereignty through the instruments of regulation of foreign direct investment (FDI) policy.Methods: the study involved general scientific methods, including analysis, synthesis and comparison. Tables were used to systematize the presentation of the results. A graphical method was used to visualize the measurements.Results: based on the analysis of economic, political and organizational factors that hinder ensuring technological sovereignty, the problems of regulating the general policy of the European Union in the field of foreign direct investment are identified. An assessment of the instruments is carried out. The weaknesses of the EU approach to regulating direct investment are shown to strengthen the Union's technological sovereignty.Conclusions and Relevance: the study found that the current EU approach to FDI policy and the instruments used within it have insufficient impact on strengthening European technological sovereignty. To be more effective in attracting and distributing funding for strategically important projects, the EU focuses on promoting framework programs. However, the key barrier here is the limited overall budget. The political agenda of the EU aims to diversify partners, but their range is limited by national security considerations, which is unlikely to contribute to actual diversification. European control over mergers and acquisitions will probably reduce this type of investment to a minimum, but the construction of industrial enterprises, infrastructure facilities and other FDI that contribute to both the actual development of the host country and bring benefits to the investor are generally welcomed. Given the new conditions for FDI, one should not expect a large number of incoming investment flows to the EU, but their benefit for strengthening technological sovereignty will be greater.